THE SATISFACTION OF TODDLER’S MOTHER TOWARD THE USE OF THE E-POSYANDU KESEHATAN (E-POK) APPLICATION IN ISLAND TERRITORY - Nurul Aini Suria Saputri; Melly Damayanti; Nur Cahya Rachmawati (International Journal of Social Science, 2022)
COVID-19 has been declared as a global pandemic by WHO (World Health Organization). The government has regulated several important points regarding to the routine services, including the elimination of services for toddlers at posyandu where monitoring is carried out independently at home using the KIA handbook by the mother or family. This causes the lower participation of toddler’s mothers to visit posyandu in the island territory. The researchers are interested in designing an application that can be used as an alternative way to monitor the growth and development of toddlers for those who cannot attend at posyandu either because of the COVID-19 pandemic or the limited access. This study aims to determine the satisfaction of using Android-based e-Posyandu Kesehatan (e-PoK) application as an alternative posyandu in the island territory. This study used a quasi-experimental design with one-group posttest-only design. A total of 138 respondents were taken by proportional stratified random sampling. The data obtained were analyzed univariately. Based on the results of the study, the category of respondents' satisfaction with the ePoK application was mostly satisfied category (92.75%). Based on these results, it is expected that toddlers’ mothers can utilize the advantage of e-PoK application to monitor the growth and development of their toddlers as an alternative way to do posyandu.